Simulation of Calcium Phosphate Species in Aqueous Solution: Force Field Derivation - Demichelis, R.; Garcia, N.; Raiteri, Paolo; Innocenti Malini, R.; Freeman, C.; Harding, J.; Gale, Julian (American Chemical Society, 2017)
A new force field has been derived for the aqueous calcium phosphate system that aims to reproduce the key thermodynamic properties of the system, including free energies of hydration of the ions and the solubility of the solid mineral phases. Interactions of three phosphate anions (PO 3-, HPO 2- and H PO -) with water were calibrated through comparison with the results 4424 obtained from ab initio molecular dynamics using both GGA and hybrid density functional theory with dispersion corrections. In the solid state, the force field has been evaluated by benchmarking against experiment and other existing models and is shown to reproduce the structural and mechanical properties well, despite the primary focus being on thermodynamics. To validate the force field, the thermodynamics of ion pairing for calcium phosphate species in water has been computed and shown to be in excellent agreement with experimental data.